Phytodiversity and population status of coastal flora of Jamnagar district and its Islands in the Gulf of Kachchh, Gujarat - Das, L; Kamboj, RD (Indian Forester, 2020)
The present research work aimed to study the diversity, distribution and population attributes of plant species (trees, shrubs and herbs) in coastal areas of Jamnagar District and its islands in the Gulf of Kachchh. During the data collection random sampling method was employed. A total of 213 coastal floral species belonging to 56 families and 157 genera were recorded. Out of these 213 plant species, 101 species of herbs, 38 species of under-shrubs and shrubs, 30 species of climbers were recorded. Grasses and sedges were also represented by 30 species and 14 species were of trees. Among the herb species, Aeluropus lagopoides showed the highest density (5.37 ind./Km2) and frequency (35.5%). Regarding tree and shrub species, Prosopis juliflora represented the highest density (516.58 ind./ha) and frequency (61.76%). Moreover, the highest importance value index was measured in Aeluropus lagopoides (42.48) among herbs and Prosopis juliflora (122.36) among trees and shrubs. The present study also deals with Î± diversity (Shannon diversity index, Simpson’s Index, species richness, evenness index) of the coastal terrestrial plants. The Abundance/Frequency ratio of trees, shrubs and herb species showed contagious distribution pattern. This study provides baseline information on the phytodiversity of coastal flora of Jamnagar and its islands